FROM A DISTANCE STANDING UP VILLAGE FARM OF LAND TODAY'S STATUS DETERMINATION ISSUES (American Journal of Pedagogical and Educational Research, 2023)
Village to the farmer don't drive land, reserve land, estate lands, surroundings the forest regions, many yearly fields, hayfields, pastures enters _ A lot yearly fields-planted trees, bushes and herbaceous plants ( gardens , vineyards , berries fruity fields ) occupied by _ land plots .